PENGARUH PERMAINAN BEREGU DAN JENIS KELAMIN TERHADAP PENINGKATAN KESEGARAN AEROBIK - Agus Supriyoko (Jurnal Ilmiah Spirit, 2011)
The purpose of this study is to determine: (a) Effect of team games to increase aerobic fitness student sons and daughters of grade IV and V SD Muhammadiyah 1 Surakarta academic year 2004/2005. (2) The difference of the influence of team games to increase aerobic fitness between boys and girls grade IV and V SD Muhammadiyah 1 Surakarta academic year 2004/2005. To achieve the above objectives used the experimental method, namely to investigate whether there is any treatment effect is tested. The experiment was conducted in an SD Muhammadiyah 1 Surakarta. Total sample of 30 children from a population of 249 students grouped by gender. Treatment was given 3 times a week seelama six weeks and carried out gradually sesuuai with treatment programs that have been determined. Data collected by the test and measurement techniques Modified Harvard Step Test. Engineering data analysis techniques with statistical analysis using t test at 5% level of significance. Based on the results of data analysis concluded the following things: (1) There is the influence of team games to increase aerobic fitness in students the children of class IV and V SD Muhammadiyah Surakarta year 2004/2005, with t count equal = 8.269134473 and t table value 1701. (2) There are differences in the effect of team games to increase aerobic fitness in boys and girls grade IV and V SD Muhammadiyah 1 Surakarta year 2004/2005, with t count equal = 0.086716172 and t tables for 1701. So the t count equal <t table.